Applications of cell penetrating peptide-based drug delivery system in immunotherapy - Du, Jing-Jing; Zhang, Ru-Yan; Jiang, Shangchi; Xiao, Shanshan; Liu, Yiting; Niu, Yongheng; Zhao, Wen-Xiang; Wang, Dongyuan; Ma, XianShi (Frontiers in Immunology, 2025)
Cell penetrating peptides (CPPs) are usually positive charged peptides and have good cell membrane permeability. Meanwhile, CPPs are facile to synthesize, and can be functionalized to satisfy different demands, such as cyclization, incorporating unnatural amino acids, and lipid conjugation. These properties have made them as efficient drug-delivery tools to deliver therapeutic molecules to cells and tissues in a nontoxic manner, including small molecules, DNA, siRNA, therapeutic proteins and other various nanoparticles. However, the poor serum stability and low tumor targeting ability also hindered their broad application. Besides, inappropriate chemical modification can lead to membrane disruption and nonspecific toxicity. In this paper, we first reviewed recent advances in the CPP applications for cancer therapy via covalent or non-covalent manners. We carefully analyzed the advantages and disadvantages of each CPP modifications for drug delivery. Then, we concluded the recent progress of their clinical trials for different diseases. Finally, we discussed the challenges and opportunities CPPs met to translate into clinical applications. This review presented a new insight into CPPs for drug delivery, which could provide advice on the design of clinically effective systemic delivery systems using CPPs.